When outcome is a balance: methods to measure combined utility for the choice between induction of labour and expectant management in mild risk pregnancy at term - Mol Ben WJ; Birnie Erwin; Bijlenga Denise; Bonsel Gouke J (BMC, 2007)
Abstract Background When the primary and secondary outcomes of clinical studies yield ambiguous or conflicting recommendations, preference or valuation studies may help to overcome the decision problem. The present preference study is attached to two clinical studies (DIGTAT, ISRCT10363217; HYPITAT, ISRCT08132825) that evaluate induction of labour versus expectant management in term pregnancies with a mild risk profile. The purpose of the present study is to compare four methods of valuation/preference measurement. Methods Multidimensional health state descriptions ('vignettes') defined by attributes and levels are presented to different response groups: laypersons, (ex-) patients, and medical experts. Valuations/preferences are measured with the Visual Analogue Scale (VAS), Time Trade-Off (TTO), Willingness to Pay (WTP) and Discrete Choice Experiment (DCE) techniques. These methods are compared in terms of feasibility, reliability and validity. Anticipated results By comparing the four techniques, we aim to answer (1) which of the techniques is most feasible, reliable and valid for use in multidimensional decision problems; (2) which of the techniques can be recommended for use in economic evaluations, and (3) do different response groups produce systematically different valuations, and if so, how can these be used to interpret preference results and to contribute to the development of clinical guidelines.